The Human Genome and Gene “Therapy”: Some Ethical Issues - D. Knapp van Bogaert; G.A. Ogunbanjo (South African Family Practice)
The major scientific achievement of the Twentieth Century was the discovery of the double helix, and the mapping of the human genome in 2003. Contemporary medical and scientific knowledge in the field of gene therapy has the potential to inform us about many of the known inherited genetic conditions. In addition, medicine now has the ability to identify a significant number of diseases which may be inherited from us by our children. When we discuss the ethics of gene therapy, a distinction should be made between somatic (non-reproductive) and germ (reproductive) cell therapies. In this article, we focus on the ethical issues related to prenatal screening for genetic disorders which include autonomy, cost and maternal anxiety.